Aspectual Functions of the Verbal Prefix a- in Old English with Reference to Gothic - Broz, Vlatko (Array, 2012)
This paper is a corpus-based study of the Old English verbal prefix a- which is no longer productive in English today, but survives in a few lexical relics such as arise, awake or ashamed. After a brief discussion of hardly any previous research and its etymology, the paper investigates a range of meanings and functions that the verbal prefix a- had in early English, showing that it was in an advanced stage of grammaticalization and that its primary function was to express perfective aspect. The prefix is contrasted with its cognate in Gothic, as well as its equivalents in Modern English and Croatian, a Slavic language that marks aspect morphologically.